2021
DOI: 10.1002/que2.80
|View full text |Cite
|
Sign up to set email alerts
|

Variational quantum packaged deflation for arbitrary excited states

Abstract: Determining the spectral structure of molecular Hamiltonians is one of the most important and challenging research fields in quantum chemistry. In the near future, such a problem may be solvable by means of quantum simulation. However, constrained by a handful of qubits and noisy quantum gates available in the near‐term quantum devices, hybrid quantum‐classical algorithms based on variational methods such as variational quantum eigensolver have become a preferable choice. Here we propose an interesting variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Comparison results showed that the proposed comparators have an overall advantage over the known comparators without quantum measurements for T-count, T-depth, CNOT-count, and circuit width. Some algorithms have been proposed for NISQ devices [40], [41]. For instance, a quantum convolutional neural network (QCNN) on NISQ devices is implemented by multiple control gates [41].…”
Section: Discussionmentioning
confidence: 99%
“…Comparison results showed that the proposed comparators have an overall advantage over the known comparators without quantum measurements for T-count, T-depth, CNOT-count, and circuit width. Some algorithms have been proposed for NISQ devices [40], [41]. For instance, a quantum convolutional neural network (QCNN) on NISQ devices is implemented by multiple control gates [41].…”
Section: Discussionmentioning
confidence: 99%
“…In summary, we propose a robust quantum search algorithm with both the advantage of simple search operators, and high success rate over a wide range of values. Therefore, it provides many potential applications [ 28 , 29 , 30 , 31 , 32 ] in future quantum computing.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the extension of the VQE algorithm to the excited state is not trivial, as a variational estimation of the excited-state energies can only be defined under orthogonal constraints. Such constraints have been considered by adding penalization terms to the Hamiltonian, thus leading to the state-specific variational quantum deflation (VQD) algorithm where each state is determined by a separate minimization (or only two minimizations in total if the first one is performed on a state-average ensemble). Other extensions can treat excited states on the same footing, but still favor the ground state. However, the proper description of conical intersections or avoided crossings requires a democratic description of both the ground and excited states.…”
Section: Theorymentioning
confidence: 99%